Synthesis, Characterization and Applications of Polymer Nanocomposites: Advances in the development and utilization of polymer nanocomposites (Journal of Advances and Scholarly Researches in Allied Education, 2023)
For specialized applications in today's modern world, a variety of multifunctional materials withsuitable mechanical, thermal, electrical, and chemical properties are required. Composites are a type ofmaterial that offers a lot of potential for developing multifunctional innovative materials that are neededfor new technological developments.Composite materials can provide a desirable set of qualities that can be adjusted to meet the uniquerequirements for a given application by mixing two chemically or physically distinct materials.Traditional materials such as metals, ceramics and metal alloys, polymers, and other materials cannotachieve such a mix of qualities. Lately, polymer nanocomposites have been making waves in the mediaand in a variety of industries. There has been a lot of interest in tailoring the structure and compositionof materials on a nanometer scale in the last several years. As a result, a thorough examination of thesynthesis, characteristics, and applications of polymer nanocomposites is critical. Polymernanocomposites are divided into several types based on a variety of factors. Sol gel process, in-situpolymerisation, solution mixing process, melt mixing process, and in-situ intercalative polymerisationare some of the preparation processes. Mechanical, optical, rheological, flame retardancy, and dielectricbehaviour of nanocomposites have all been thoroughly examined. Finally, the major uses ofnanocomposites as well as their future prospects have been discussed.